Posterior Tracheopexy for Severe Tracheomalacia Associated with Esophageal Atresia (EA): Primary Treatment at the Time of Initial EA Repair versus Secondary Treatment - Shieh, Hester F.; Smithers, C. Jason; Hamilton, Thomas E.; Zurakowski, David; Visner, Gary A.; Manfredi, Michael A.; Baird, Christopher W.; Jennings, Russell W. (Frontiers in Surgery, 2018)
Purpose We review outcomes of posterior tracheopexy for tracheomalacia in esophageal atresia (EA) patients, comparing primary treatment at the time of initial EA repair versus secondary treatment. Methods All EA patients who underwent posterior tracheopexy from October 2012 to September 2016 were retrospectively reviewed. Clinical symptoms, tracheomalacia scores, and persistent airway intrusion were collected. Indication for posterior tracheopexy was the presence of clinical symptoms, in combination with severe tracheomalacia as identified on bronchoscopic evaluation, typically defined as coaptation in one or more regions of the trachea. Secondary cases were usually those with chronic respiratory symptoms who underwent bronchoscopic evaluation, whereas primary cases were those found to have severe tracheomalacia on routine preoperative dynamic tracheobronchoscopy at the time of initial EA repair. Results A total of 118 patients underwent posterior tracheopexy: 18 (15%) primary versus 100 (85%) secondary cases. Median (interquartile range) age was 2 months (1–4 months) for primary (22% type C) and 18 months (8–40 months) for secondary (87% type C) cases (p < 0.001). There were statistically significant improvements in most clinical symptoms postoperatively for primary and secondary cases, with no significant differences in any postoperative symptoms between the two groups (p > 0.1). Total tracheomalacia scores improved significantly in primary (p = 0.013) and secondary (p < 0.001) cases. Multivariable Cox regression analysis indicated no differences in persistent airway intrusion requiring reoperation between primary and secondary tracheopexy adjusting for imbalances in age and EA type (p = 0.67). Conclusion Posterior tracheopexy is effective in treating severe tracheomalacia with significant improvements in clinical symptoms and degree of airway collapse on bronchoscopy. With no significant differences in outcomes between primary and secondary treatment, posterior tracheopexy should be selectively considered at the time of initial EA repair.